A8.38 MMF treatment differentially regulates immune responses to vaccination by PNEUMOVAX but not prevnar in MRL/LPR mice. (31st January 2014) - Gazivoda, Victor; Mehta, Shikha; Wang, Luhan; Sperber, Kirk; Tassiulas, Ioannis
Abstract : Background and Objectives: Infections are a major cause of morbidity and mortality in patients with systemic lupus erythematosus (SLE) treated with immunosuppressive therapy. Mycophenolate mofetil (MMF) blocks the proliferation of activated B and T lymphocytes and is a common immunosuppressive used in the treatment of SLE. PneumoVax is a 23valent unconjugated pneumococcal polysaccharide vaccine and Prevnar is a 13valent pneumococcal polysaccharide vaccine conjugated to a protein carrier (a nontoxic recombinant variant of Diphtheria toxin). Currently it is not known if the conjugated polysaccharide pneumococcal vaccine is more effective in eliciting stronger antibody responses in patients that are treated with immunosuppressive treatments and more specifically MMF. We evaluated immune responses elicited by the two pneumococcal vaccines in the MRL/lpr mouse model of SLE and the effect of MMF treatment. Materials and Methods: Eight week old MRL/lpr mice were purchased from Jackson +Laboratories (Bar Harbor, ME). Six groups of mice (5 in each group) were studied, 3 groups received MMF (100 mg/kg of body weight) in standard mouse chow while 3 groups were left untreated. The mice were then vaccinated with PneumoVax and/or Prevnar (0.05ml, intra-peritoneal) or left unvaccinated. Eight weeks later the mice were sacrificed. The serum was collected and analysed in a custom made ELISA for the presence of specific pneumococcal polysaccharide antibodies. T and B lymphocytes were stimulated with anti-CD3/CD28 and TLR ligands respectively and cytokine production was analysed with specific ELISA assays. Results: MMF treated and untreated MRL/lpr mice vaccinated with Pneumovax and Prevnar developed comparable levels of specific IgM pneumococcal polysaccharide antibody titers. Anti-polysaccharide IgG antibody titers decreased significantly in the MMF-treated group that received Pneumovax (p<0.0278), while it was not affected in the MMF-treated group that received Prevnar. The effect of MMF treatment on T cell production of IL-4 and IFN-g differed between the mice that received Pneumovax vs Prevnar. Mice that received Pneumovax and MMF produced increased amounts of IFN-g after T cell stimulation while IL-4 production was inhibited. Prevnar vaccinated and MMF-treated mice showed no significant difference in T cell cytokine production. Conclusions: MMF treatment inhibited IgG antibody responses directed against pneumococcal polysaccharides in MRL/lpr mice vaccinated with Pneumovax but not Prevnar. Moreover, the effect of MMF treatment on the T cell cytokine responses in mice vaccinated with Pneumovax vs Prevnar differed in the production of IL-4 and IFN-g, major cytokines for the regulation of specific antibody responses by B cells.